Memahami Keberadaan Street Vendors di Jalan Samudera 1 Kota Lhokseumawe - M A Pahlafy; Deni; E Saputra (Cered Indonesia Institute, 2024)
Lhokseumawe City is a city in the province of Aceh, this city is right in the middle of the eastern route of Sumatra, from the past until now the City of Lhokseumawe has always attracted interest as a place of business due to its strategic location. However, the high cost of renting buildings or land is a major problem for some people. So that the use of public space becomes a solution for creative economy actors. Street Vendors is one of the phenomena in urban areas that has been discussed by many scholars in the urban informal sector. This Study Focus on the characteristics, and stratergy street vendors. Many scholars supported that the axistences of informal street vendors. In urban space contributes to a positive impact on the sustainability of urban life. Mixed – Method research approach is applied in this study to analys the descriptive and qualitative data obtained through observation, mapping, photo, and interviews seller at Jalan Samudera 1 lhokseumawe City.